Development of a High‐Pressure Reactor Based on Liquid‐Flow Pressurisation to Facilitate Enzymatic Hydroxylation of Gaseous Alkanes. Issue 19 (27th August 2019) - Ariyasu, Shinya; Kodama, Yusaku; Kasai, Chie; Cong, Zhiqi; Stanfield, Joshua Kyle; Aiba, Yuichiro; Watanabe, Yoshihito; Shoji, Osami
Abstract: A new type of high‐pressure reactor based on liquid‐flow pressurisation using a HPLC pump has been developed. This high‐pressure reactor allows the easy and safe performance of reactions with gaseous alkanes under high‐pressures up to 10 MPa (100 atm), without the need for high‐pressure gas cylinders. The amount of substrate gas required for a single reaction is very small compared with reactions using a conventional autoclave, which, when using expensive substrate gasses, such as 13 C‐labelled ethane, becomes critical. Employing this high‐pressure reactor in conjunction with cytochrome P450BM3 and the assistance of decoy molecules, the direct hydroxylation of gaseous alkanes was drastically improved. At 5 MPa the TOF of propane hydroxylation increased 10‐fold, reaching 2200 min −1 . Hydroxylation of ethane was also substantially accelerated at 5 MPa, reaching a TOF of 28 min −1 . Abstract : It's all in flow ! A novel high‐pressure reactor based on liquid‐flow pressurisation using HPLC pump has been developed. Direct hydroxylation of gaseous alkanes by cytochrome P450BM3 with assistance of decoy molecules was drastically improved using this high‐pressure reactor. The TOF of propane‐hydroxylation was reached 2200 /min under 5 MPa of propane. Ethane hydroxylation was also greatly accelerated and the TOF reached 28 /min.